Thirst sensitivity to post-exercise fluid replacement needs and controlled drinking - Capitán Jiménez, Catalina (2014)
artículo (preprint) -- Universidad de Costa Rica, Centro de Investigación en Ciencias del Movimiento Humano, 2014